2022
DOI: 10.1111/jonm.13796
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' perceptions of their career—An interview study

Abstract: Aim We aim to explore registered nurses' perceptions of their career. Background Career development options have been found to increase attraction to nursing and support nurses' engagement with their organization and profession. Methods We collected qualitative individual interviews with 23 registered nurses; data were analysed with thematic analysis and reported according to the consolidated criteria for reporting qualitative research (COREQ) criteria. Results Three themes emerged: career choices, career enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This study examined nurses’ perceptions of job fulfillment and motivation, as well as their willingness to actively choose to take on the nursing role in the event of a conflict between family roles and time allocation. Nurses expressed that their motivation towards professional development was connected to the meaningful work they gained from their work, which is consistent with the results of previous studies [ 51 ]. Nurses’ intrinsic autonomy must be stimulated to develop and nurture this behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study examined nurses’ perceptions of job fulfillment and motivation, as well as their willingness to actively choose to take on the nursing role in the event of a conflict between family roles and time allocation. Nurses expressed that their motivation towards professional development was connected to the meaningful work they gained from their work, which is consistent with the results of previous studies [ 51 ]. Nurses’ intrinsic autonomy must be stimulated to develop and nurture this behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Some nurses felt that others’ perceptions of nursing roles could be considered one of the factors influencing their professional self-concept. Kallio et al [ 51 ] found that these perceptions significantly affected nurses’ physical and mental health and influenced their job retention. Negative perceptions of nurses’ roles by others may lead to role conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…Y. K. envisions a legacy that generates new knowledge through research. When mentors and faculty place a heavy emphasis on graduate nurses pursuing the traditional or "correct" pathway, students may become inhibited or discouraged from exploring the diverse, alternative career pathways that are available (Kallio et al, 2022). Y. K. learned about many nurses who were interested in research or other nontraditional nursing roles early in their careers but were required to gain hospital experience first, lost their interest, changed professions altogether, or were encouraged to pursue traditional graduate degrees instead.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, the limited opportunities for advancement in professional careers hinder the possibility of transitioning to different roles within the nursing profession. 8 This further contributes to reducing the level of nurses' satisfaction and, therefore, their well-being. Often, the focus is on retention at the staff nurse level, where a shift to mentoring or guiding nurses toward professional growth may improve satisfaction and enhance retention.…”
Section: Nursingmentioning
confidence: 99%
“…Even if the association between nurses' well-being and earning can be variable according to the different countries, we cannot ignore that the lack of an “economic gain” proportionate to the level of professional responsibilities plays an important role in this issue 7 . Furthermore, the limited opportunities for advancement in professional careers hinder the possibility of transitioning to different roles within the nursing profession 8 . This further contributes to reducing the level of nurses' satisfaction and, therefore, their well-being.…”
Section: “Nursing”mentioning
confidence: 99%